The pre-service preparation of secondary school mathematics teachers: a case study of curriculum effectiveness - Msomi, Dumile Dennis (Rhodes University, Faculty of Education, Department of Education, 1995)
The quality of education in most historically black schools is a source of concern for many people. The high failure rate in mathematics in particular, is believed to result in part, from the inadequacy of the teacher preparation programs at many of the colleges of education in the country. Esikhawini College of Education in KwaZulu-Natal is one of the colleges which is involved in the preparation of secondary school mathematics teachers. The appropriateness of the mathematics curriculum of this College was the subject of the study. In particular, the study aimed at the following: (i) To analyse aims and philosophies underlying the prescribed mathematics curriculum of the College. (ii) To establish the teacher educators' and student teachers' perceptions of the appropriateness of the curriculum in general. (iii) To establish the teacher educators' and student teachers' perceptions of the mathematics curriculum content and processes. (iv) To establish the quality of available materials used at the College for realisation of the curriculum goals. (v) To offer proposals and recommendations for the improvement of the education of prospective secondary mathematics teachers. Data about the perceptions of the appropriateness of the mathematics curriculum was gathered through a questionnaire which was administered to one hundred and one student teachers. The issues that arose from the questionnaire study were followed up by an interview study. The interview schedule was administered to a sample of fourteen student teachers and all six mathematics teacher educators in the College. In addition, a survey of mathematics materials available at the College library and in the mathematics department was carried out to collect further data. Some of the significant findings of the, study were : "¢ Limitations in the College mathematics curriculum in as far as the curriculum content and processes were concerned. "¢ Inadequacy of mathematics curriculum materials that were available and used at the College. "¢ Low attainment in mathematics at matriculation level of most of the student teachers. "¢ Widespread dissatisfaction with the curriculum, especially that of Mathematics Didactics. The implications of the findings for the College were considered. Amongst other suggestions is the suggestion that the College introduces a preliminary STD course in which prospective student teachers' mathematics background is enriched to enable them to cope with the demands of the College curriculum.
Keywords: Mathematics -- Study and teaching (Secondary) -- South Africa -- Curricula; Mathematics teachers -- Training of -- South Africa -- KwaZulu-Natal; Esikhawini College of Education